2022
DOI: 10.1088/1361-6528/ac5e70
|View full text |Cite
|
Sign up to set email alerts
|

Switching-behavior improvement in HfO2/ZnO bilayer memory devices by tailoring of interfacial and microstructural characteristics

Abstract: We investigated the effect of top contact interface and microstructural characteristics of the insulating layers on resistive switching behaviors by fabricating and characterizing the HfO2/ZnO bilayer heterostructures. Different thickness of ZnO underlying layer and different deposition temperatures of the upper HfO2 layer were designed to analyze the intrinsic contribution of the crystalline microstructure of the insulating bilayer. Pt and Ti top electrodes were used to demonstrate the extrinsic contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…As known, Gibbs free energy has an important role in RS mechanism [8,42,43]. Based on the Gibbs free energy description, oxygen exchange between ZrO 2 and SnO 2 SLs, the lower Gibbs free energy oxides contain a higher number of oxygen vacancies [30,43,44]. The Gibbs free energy for oxide formation in the ZrO 2 and SnO 2 are ∆G o = −1100 kJ mol −1 and ∆G o = −842.91 kJ mol −1 , respectively [28,43].…”
Section: Conduction Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…As known, Gibbs free energy has an important role in RS mechanism [8,42,43]. Based on the Gibbs free energy description, oxygen exchange between ZrO 2 and SnO 2 SLs, the lower Gibbs free energy oxides contain a higher number of oxygen vacancies [30,43,44]. The Gibbs free energy for oxide formation in the ZrO 2 and SnO 2 are ∆G o = −1100 kJ mol −1 and ∆G o = −842.91 kJ mol −1 , respectively [28,43].…”
Section: Conduction Mechanismsmentioning
confidence: 99%
“…Furthermore, low oxygen partial pressure, high annealing temperature and N 2 annealing atmosphere are beneficial for the formation of oxygen vacancy [35,36]. It can be inferred that when the Gibbs free energy is low, there is a higher concentration of oxygen vacancies [30,43,44]. Additionally, a bilayer structure with a concentration gradient of oxygen vacancies can be advantageous for components operating through the VCM mechanism.…”
Section: Conduction Mechanismsmentioning
confidence: 99%
“…丝通道又分为金属离子导电桥 [36,37] 和氧空位( ) 导电细丝 [38−40] 两种. 由于Ag离子质量远大于氧 41] )小于 迁移率(~3.5× 10 -9 cm 2 •V -1 •s -1 [42] ), 因 此 通 常 需 要 较 大 的 form-ing电压(~3.5 V) [43] 才能形成Ag离子导电桥, 而 且器件的翻转电压也相对较大( >1 V) [44,45] .…”
Section: Hfo 2 /Niounclassified
“…On the other hand, the metal/oxide interface is significant for the formation and dynamics of V O and thus many efforts have been carried out to engineer the interfaces to optimize the multilevel RS and the reliability. For example, Ti [10], TiO x buffer layers [11], plasma-enhanced [12][13][14] and electrode treatments [14,15] have been demonstrated to be able to engineer interfacial defects to improve the device reliability and analog switching. Moreover, recently it is reported that bilayer or multilayer HfO 2 stacks using AlO x [16][17][18][19], TiO x [20,21], ZrO x [22], ZnO [15] insert layers to form hetero metal-oxide interfaces show excellent performances for multilevel RS, thanks to the possible control and confinement of CFs at interface in such heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ti [10], TiO x buffer layers [11], plasma-enhanced [12][13][14] and electrode treatments [14,15] have been demonstrated to be able to engineer interfacial defects to improve the device reliability and analog switching. Moreover, recently it is reported that bilayer or multilayer HfO 2 stacks using AlO x [16][17][18][19], TiO x [20,21], ZrO x [22], ZnO [15] insert layers to form hetero metal-oxide interfaces show excellent performances for multilevel RS, thanks to the possible control and confinement of CFs at interface in such heterostructures. Among them, HfO 2 /Al 2 O 3 bilayer turns out to be the most interesting candidate for the application of neuromorphic hardware due to the compatibility with industrial mass fabrication.…”
Section: Introductionmentioning
confidence: 99%